Antisperm antibodies disrupt plasma membrane integrity and inhibit tyrosine phosphorylation in human spermatozoa (Faculty of Medicine Universitas Indonesia, 2018)
Background: The etiology of unexplained infertility has not been fully understood. This study aimed to determine the effect of antisperm antibody (ASA) from infertile women on viability, motility, plasma membrane integrity, and status of tyrosine phosphorylation in the human spermatozoa.Methods: An experimental in vitro study was conducted at the Department of Biology, Faculty of Medicine, Universitas Indonesia from February to November 2014. Spermatozoa from normal fertile donors was incubated with serum containing ASA from infertile women at several dilutions (1/1000, 1/100, 1/10, and without dilution) for 1 and 2 hours. The plasma membrane integrity was assessed with hypoosmotic swelling (HOS) test, whereas the status of tyrosine phosphorylation was analyzed using Western immunoblotting and immunocytochemistry.Results: After 1 hour incubation time, ASA caused a decrease in sperm viability, motility, plasma membrane integrity, and inhibit sperm tyrosine phosphorylation. ASA caused a decrease in viability, motility, sperm plasma membrane integrity, and tyrosine phosphorylation of sperm after 1 hour incubation time.Conclusion: ASA from infertile women reduced the sperm viability, motility, plasma membrane integrity, and capacitation in dose and time dependent manner.